Refuse Derived Fuel Production through Biodrying Process (Case study: Solid Waste from Canteens) (Universitas Negeri Semarang, 2020)
Due to its calorific value, wastes could be treated into Refuse Derived Fuel (RDF) through several processes. In order to get higher calorific value, moisture content in the wastes could be removed by utilizing the heat generated from decomposition of organic fraction by microorganism (biodrying process). The study aims to treat solid wastes generated from canteens in Ganesha Campus of Institut Teknologi Bandung into RDF through biodrying process. Through standard sampling procedure, total waste generated from 59 canteens was 228 kg/day and organic fraction became the dominant (74%). There were 3 biodrying piles prepared, namely aeration, windrow, and control pile. Temperature in all piles increased in first and second weeks, then it gradually decreased and the average temperature were between 23-48 oC. The heat generated during the process could be remove water content and the optimum time 17-22 days could reach 20-30% of moisture content. The highest calorific value could be obtained from aerated pile (14.98 MJ/kg). By considering several parameters, the best RDF were produced from aerated pile. The parameters which still did not comply with the international standard of RDF were ash content, fixed carbon, and organic carbon. The quality of RDF was affected significantly by the composition of the feed. Though it could not meet with all parameters as an international standard of RDF, the product could be used as co-fuel to substitute coal or other fossil fuels for industrial activities. By knowing that the wastes could be converted into valuable product, the local municipality may shift the conventional paradigm of the waste management which is only collect-haul-dispose into a new paradigm by prioritizing waste recycle.